Realisasi Perlindungan Anak Telantar Oleh Pemerintah Daerah Kota Bandar Lampung - Tio Haikal Anugerah; Dian Herlambang (Universitas Sang Bumi Ruwa Jurai, 2018)
AbstractChildren are inseparable part of human sustainability and the sustainability of a nation. In order to be able to be responsible for the sustainability of the state, every child needs to get the widest possible opportunity to grow and develop optimally, both physically, mentally and socially. For this reason, protection measures are needed to realize the welfare of the children by providing guarantees for the fulfillment of their rights without discriminatory treatment. The presence of the Regional Government as a subject who later participated in the implementation of children protection is what later attracted the attention of the authors to research related to the role of Local Government which in this study was purified only to the local government of Bandar Lampung City on the implementation of child protection which also limited its scope to abandoned children. This research intends to reveal how the realization of the protection of abandoned children by the local government of Bandar Lampung City. Then, researchers also want to see whether the policies taken by the local government of Bandar Lampung City are effective or not. The results showed that de facto, the implementation of children protection in Bandar Lampung City had not been optimally implemented. Based on data from the Social Service of Bandar Lampung City, the number of abandoned children in Bandar Lampung amounted to 1229 inhabitants per 2015, aka nearly double the number in 2011 which amounted to only 614 people. If viewed through Soerjono Soekanto's law enforcement effectiveness theory as described earlier, the author argues that the true cause of the ineffectiveness of abandoned child protection is not due to legal factors, but to law enforcement factors, facilities and infrastructure factors, community factors and cultural factors.